Perlindungan Terhadap Tenaga Kesehatan di Masa Adaptasi Kebiasaan Baru Selama Pandemi Covid-19 - patandianan, alan crispapanrio (Universitas HKBP Nommensen, 2021)
Background: The spread of the Covid-19 disease that occurred at the end of 2019 had many impacts on society, including health workers. Therefore, efforts to protect against the dangers of Covid-19 are needed in the workplace so that the safety and health of workers is guaranteed. The application of a hierarchy of hazard control is an example of a method that can be applied. Goal: To determine the application of methods of protecting health workers in the adaptation period for new habits during the Covid-19 pandemic. Method: The making of a Literature Review was carried out with a literature review with a descriptive approach based on relevant research articles or journals. Search scientific literature on PubMed electronic database using the keyword